Upper eyelid contour measurement in an Asian population using Bézier curve analysis - Da Young Shin; Won-Kyung Cho; Ji-Sun Paik; Suk-Woo Yang (PLoS ONE, 2025)
Purpose To define and quantify the upper eyelid contour of normal Asian adults using a software program utilizing Bézier curves. Methods Eighty eyes of 80 healthy Korean subjects were included in this study. The Bézier curve tool of Image J software was used to extract the upper eyelid contours. The x and y coordinate values of the four points of the Bézier curve were analyzed using graphical analysis software in Matlab. Various parameters were measured automatically using a custom-written software algorithm. Results The Bézier curves showed an excellent level of inter-rater reliability (intraclass correlation coefficient of 0.97 for absolute agreement, two-way random effects model, 95% CI 0.94 to 0.98). The Bézier curve for Asians was drawn from the medial palpebral commissure to the lateral canthus. The eye width was 24.8±1.8 mm in women and 25.3±2.0 mm in men. The contour peak was located at 1.7±1.0 mm temporally from the pupil center in women and 1.5±1.3 mm in men, and the height was 4.7±0.7 mm in women and 3.8±0.9 mm in men. The palpebral fissure obliquity (angle of the line connecting the medial canthal end to the lateral canthal end) was 9.98±3.07° in women and 7.52±2.89° in men. Conclusion The upper eyelid contour was measured simply and efficiently using a Bézier curves function. The main features of Asian upper eyelid contour are that the inner part of the medial canthus is covered by the eyelids, and the lateral endpoint is located higher than the medial endpoint.